Analysis of the Stabilization System of Mimbot Biped - M.E. Escobar (Journal of Applied Research and Technology, 2012)
Mimbot robot consists of a mechanical system with one degree of freedom activated by a single motor; this robot iscapable of simulating the human gait. Mimbot has three essential mechanisms: the Chebyshevmechanism, the pantograph mechanism and a stabilization system. The studied mechanism is an articulated system of links used inthe leg of of the Mimbot biped robot. The technology used in the Mimbot biped is characterized by keeping these design conditions; using a mechanical system based on classical mechanics, the biped must reproduce the trajectory of human gait, energy consumption should be minimal and the prototype should be a low-cost robot. The role of the original stabilization system is to guide the foot to provide support for both legs; however, the position of the foot is notcompletely parallel to the support surface, which causes variations in the trajectory of the mass center of the biped,causing loss of stability. This paper presents a study of stability in the sagittal plane of the robot, adding a newmechanism that ensures that the stabilizer link is parallel to the ground at all times. Finally, a studyof the kinematic and dynamic behavior generated by the modification has been carried out through an analyticalmodel created by Adams ® software.